2022
DOI: 10.1186/s40478-022-01463-z
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of cancer gene expression identifies repurposed drugs for diffuse intrinsic pontine glioma

Abstract: Diffuse intrinsic pontine glioma (DIPG) is an aggressive incurable brainstem tumor that targets young children. Complete resection is not possible, and chemotherapy and radiotherapy are currently only palliative. This study aimed to identify potential therapeutic agents using a computational pipeline to perform an in silico screen for novel drugs. We then tested the identified drugs against a panel of patient-derived DIPG cell lines. Using a systematic computational approach with publicly available databases o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 65 publications
3
7
0
Order By: Relevance
“…These tumors cells preferentially rely on de novo pyrimidine synthesis and methionine consumption [ 25 , 26 ]. Like others [ 41 ], we have found that DMG-H3K27M tumors also rely on de novo guanylate synthesis for survival. However, none of these seminal findings have considered how H3K27M-mediated metabolic changes are related to RT resistance.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These tumors cells preferentially rely on de novo pyrimidine synthesis and methionine consumption [ 25 , 26 ]. Like others [ 41 ], we have found that DMG-H3K27M tumors also rely on de novo guanylate synthesis for survival. However, none of these seminal findings have considered how H3K27M-mediated metabolic changes are related to RT resistance.…”
Section: Discussionsupporting
confidence: 84%
“…3 F and H). Others have observed single agent efficacy of MPA in DMG-H3K27M cells [ 41 ]. While we observed a significant reduction in total neurosphere number at endpoint in DIPGXIII cells at the highest concentration of MPA (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated the antitumor effects of TPL on glioblastoma (27). TPL was found to have inhibition of cell viability in Diffuse intrinsic pontine glioma (DIPG) patient-derived cell lines in vitro and in vivo (28). TPL was also reported to have selective cytotoxicity to patient-derived IDH1-mutated glioma cells (29).…”
Section: Discussionmentioning
confidence: 99%
“…It contains a total of 19,127 samples including 11,715 samples from 130 distinct cancers and 1,950 healthy samples from 5 vital organs (1,148 brain samples from various regions, 376 heart samples either from the left ventricle or atrial appendage, 28 samples from the kidney cortex, 110 liver samples, and 288 lung samples) that were processed from raw sequence data under the same pipeline [9]. Recent studies demonstrated the feasibility of performing integrative analysis of these samples in various tasks [1012]. For current study, 369 HCC case samples were compared against all healthy control samples (Supplementary Table S1, S2).…”
Section: Methodsmentioning
confidence: 99%